Study into Improvement of the Hatch Covers of General-Purpose Open Wagons to Provide Strength under Operational Loading Diagrams - Oleksij Fomin; Juraj Gerlici; Mykola Gorbunov; Alyona Lovska; Kateryna Kravchenko; Oleksii Burlutski; Tomas Lack (Communications - Scientific letters of the University of Zilina, 2019)
The article presents the results of research into the strength of the hatch covers of general-purpose open wagons. It was detected that strength of the standard hatch covers is not provided in operational loading diagrams. Therefore, new designs of the hatch covers for open wagons were proposed. The results of the strength calculation, implemented with the finite element method, make it possible to conclude that at basic and additional operational loading diagrams the strength values for proposed designs of hatch covers do not exceed the admissible values. The research conducted can contribute to a higher strength of the carrying structures of the bodies of general-purpose open wagons in operation, thus, guaranteeing a higher operational efficiency of the rail transport.